Knowledge of Diabetes Mellitus and Student Healthy Lifestyle Behavior: Pengetahuan Tentang Diabetes Melitus Dan Perilaku Hidup Sehat Mahasiswa - Barkah Purwanto; Nuni Ihsana; Adilah Rahmi Nashuha; Dewi Yuniasih (Ahmad Dahlan Medical Journal, 2022)
Diabetes Mellitus (DM) is one of the four priority non-communicable diseases that are WHO targets to follow up with a rising prevalence every year. Changes in unhealthy living behaviour from a young age are an important cause of DM. Medical students as the younger generation have some functions as agents of change, agents of health, and social control regarding health, including DM. Therefore it is necessary to identify the students’ knowledge level related to DM to reduce its incidence by way of healthy living behaviour.This research aims to determine the relationship between students' knowledge level and their healthy living behaviour. This research is an analytic quantitative study with a cross-sectional design. The population of this study was all students of the UAD Faculty of Medicine. The research sample was 96 students of the UAD Faculty of Medicine in the 3rd, 5th, and 7th semesters with a simple random sampling technique. The research data was taken using questionnaires and processed using the Spearman Rank statistical test. The results showed that the majority of respondents (55.2%) had a sufficient knowledge level about DM and the majority of students' healthy life behaviours were in a good category (47.9%). From bivariate analysis, it was obtained that p value = 0.04 (p < 0.05) which indicates a significant relationship between students' knowledge level and their healthy living behaviour. There is a relationship between the students' knowledge level and their healthy living behaviour Diabetes Melitus (DM) merupakan satu dari empat penyakit tidak menular (PTM) yang menjadi prioritas target tindak lanjut WHO dengan prevalensi yang terus meningkat setiap tahunnya. Perubahan perilaku hidup yang tidak sehat sejak usia muda menjadi penyebab penting dalam terjadinya DM. Mahasiswa kedokteran sebagai generasi muda memiliki fungsi sebagai agent of change, agent of health, dan social control tentang kesehatan, termasuk DM. Sehingga perlu dilakukan identifikasi tingkat pengetahuan mahasiswa terkait DM untuk menurunkan angka kejadian DM melalui perilaku hidup sehatnya. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan dengan perilaku hidup sehat mahasiswa. Penelitian ini merupakan penelitian analitik kuantitatif dengan desain cross-sectional. Populasi penelitian ini adalah seluruh mahasiswa Fakultas Kedokteran UAD. Sampel penelitian sebanyak 96 mahasiswa Fakultas Kedokteran UAD semester 3, 5, dan 7 dengan teknik pengambilan sampel proportionate stratified random sampling, Data penelitian diambil menggunakan kuesioner dan diolah menggunakan uji statistik Spearman Rank. Hasil penelitian menunjukkan mayoritas responden (55,2%) memiliki tingkat pengetahuan yang cukup mengenai DM dan mayoritas perilaku hidup sehat mahasiswa dalam kategori baik (47,9%). Analisis bivariat didapatkan nilai p = 0,04 (p < 0,05) yang menunjukkan adanya hubungan signifikan antara tingkat pengetahuan dengan perilaku hidup sehat mahasiswa. Ada hubungan antara tingkat pengetahuan mengenai DM dengan perilaku hidup sehat mahasiswa